Neutrophil to Lymphocyte Ratio in Pulmonary Tuberculosis Patients with and without Diabetes Mellitus and Human Immunodeficiency Virus Co-Infection Comorbidities - Nanlohy, Shelda Friuley; Latif, Rahmi Rifany; Ursula, Yanita Novalina; Latuconsina, Vina Zakiah; Tentua, Vebiyanti; Anggriyani, Rina (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Tuberculosis (TB) remains a leading cause of mortality in Indonesia. The presence of diabetes mellitus (DM) and human immunodeficiency virus (HIV) co-infection comorbidities is a double burden. In TB patients, the neutrophil to lymphocyte ratio (NLR) is an inflammatory marker and may indicate disease progression and immune system status. This study aimed to describe the NLR in pulmonary TB patients with and without DM and HIV co-infection comorbidities. Methods: This study used a quantitative descriptive method with a cross-sectional approach. A total sampling technique was used, resulting in a sample of 159 participants. Data were collected from medical records. Results: Among 108 newly diagnosed pulmonary TB patients in this study, 42 patients (38.9%) had a normal NLR (0.78-3.53), while 66 patients (61.1%) had an increased NLR (>3.53). Of the 28 TB patients with DM comorbidity, 12 patients (42.9%) had a normal NLR, while 16 patients (57.1%) had an increased NLR. Among the 23 TB patients with HIV co-infection comorbidity, four patients (17.4%) had a normal NLR, while 19 patients (82.6%) had an increased NLR. Conclusion: The results showed that pulmonary TB patients with and without DM and HIV co-infection comorbidities had a high NLR.